Growth and survival of Campinarana seedlings subject to drought and flooding: implications for ecological restoration - Elias, Priscila Salomão; Vieira, Daniel Luis Mascia (Plant ecology, 2020)
Campinaranas are Amazonian ecosystems that undergo seasonal drought and flooding, making seedling establishment a great challenge. In ecosystems with extreme hydrologic variation, the seeding timing may affect seedling establishment. This study evaluates germination, survival, and growth of seedlings of the Campinarana tree species Himatanthus sucuuba, Hydrochorea corymbosa, and Ruizterania retusa under drought and flooding conditions, simulating different timings of planting. Germination was evaluated in flooding and moist conditions. Seedlings underwent the following treatments in a greenhouse environment: moist followed by moist (MoMo), moist followed by flooding (MoFl), moist followed by drought (MoDr), and flooding followed by moist (FlMo), with a 90-day period for each water regime. Seedling survival, biomass, height, wilting stages, and development of morphological structures were evaluated. Seedling survival of H. sucuuba and H. corymbosa was higher than 80% in all treatments. Himatanthus sucuuba had higher growth in MoMo and H. corymbosa did not differ among MoMo, MoDr, and FlMo treatments. Ruizterania retusa had higher survival in MoMo and FlMo treatments and had higher growth in FlMo. Himatanthus sucuuba and H. corymbosa seedlings had low growth in general but were resistant to flooding up to 90 days, while 90–180-day-old seedlings took advantage of moist conditions to grow fast. Species varied widely in their performances from dry to flooded conditions after germination, suggesting that Campinarana species have different strategies to ensure seedling establishment. Timing of seeding or seedling planting could be managed to improve seedling establishment.